Massive Ameloblastomas - N. C. Misra; R. Chandra; S. Bhattacharya; A. Chaturvedi; M. S. D. Jaiswal (Indian Journal of Plastic Surgery)
Our experience in the management of eleven cases of massive ameloblastomas of the jaws seen during the last fourteen years in the department of Surgery at the King George's Medical College, Lucknow is being presented. Immediate reconstruction of the jaw was attempted with either a bone graft or a stainless steel plate or K-wires as was feasible. Of the three modalities used for reconstructing the defect, bone grafts gave the best acceptable results.